Electrochemical properties of self-assembled films of single-walled carbon nanotubes, monolayer-protected clusters of gold nanoparticles and iron (II) phthalocyanines at gold electrodes - Ozoemena, Kenneth I. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.